Regulation's Effects on the Trends in Community Antibiotic Consumption in the European Union and the United States - Saxena, Shivang; Singh, Sankushdeep; Sahoo, Nihar Ranjan; Kumar, Sushil; Sharma, Nandini; Garg, Yukta; Singh, Amandeep (Anti-Infective Agents, 2025)
This study presents the compiled information from the EU and the US on antibiotic dispensation across the countries and trends between 2011 and 2020 as per the latest available data. Antibiotic misuse continues to be a significant global health challenge, exacerbated by insufficient regulatory measures and a lack of public awareness. Utilizing data on antibiotic dispensation, we analyze the correlation between national regulatory conditions and levels of antibiotic use, with a particular focus on amoxicillin, the most frequently prescribed antibiotic. Our findings reveal that while there has been an overall decrease in amoxicillin consumption in recent years, significant disparities persist among countries. For instance, from 2015 to 2020, the U.K., France, and Germany reported some of the highest rates of antibiotic consumption, significantly above the EU average. This highlights the critical role of effective regulatory measures in mitigating overuse and promoting responsible prescribing practices. Statistical analyses indicate that robust national regulations correlate with lower rates of antibiotic consumption, underscoring the necessity for continued monitoring and policy development. The study also emphasizes the importance of future surveillance efforts aimed at preventing antibiotic overuse and addressing the growing threat of antimicrobial resistance. Overall, this study contributes to understanding how regulatory actions can shape antibiotic consumption patterns and inform strategies for improving public health outcomes in both the EU and US contexts.
Keywords: Antibiotic consumption